2008
DOI: 10.4310/cag.2008.v16.n1.a1
|View full text |Cite
|
Sign up to set email alerts
|

On a non-local curve evolution problem in the plane

Abstract: This paper deals with a new curvature flow for closed convex plane curves which shortens the length of the evolving curve but expands the area it bounds and makes the evolving curve more and more circular during the evolution process. And the final shape of the evolving curve will be a circle (as the time t goes to infinity). This flow is determined by a coupled system concerning both local and global geometric quantities of the evolving curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…The same result in the one-dimensional case was obtained by Gage [5]. Recently, a similar convergence theorem for a modified curve flow along which the isoperimetric ratio also decreases was proved by Jiang and Pan [11]. Based on center manifold analysis, Escher and Simonett [4] showed that if the initial hypersurface is sufficiently close to a fixed sphere, then the flow will converge exponentially to a round sphere.…”
Section: Introductionsupporting
confidence: 62%
“…The same result in the one-dimensional case was obtained by Gage [5]. Recently, a similar convergence theorem for a modified curve flow along which the isoperimetric ratio also decreases was proved by Jiang and Pan [11]. Based on center manifold analysis, Escher and Simonett [4] showed that if the initial hypersurface is sufficiently close to a fixed sphere, then the flow will converge exponentially to a round sphere.…”
Section: Introductionsupporting
confidence: 62%
“…Such a flow was first investigated by Jiang and Pan in . Similarly, as Mu and Zhu in , they employed the Gauss parameterization for evolution of convex curves and so results of can be applied to convex curves. In what follows, we show that some of their results (e.g., area increasing property) can be directly generalized to the case of evolution of Jordan curves by using the arc‐length parameterization.…”
Section: Evolution Of Plane Curves With a Nonlocal Normal Velocitymentioning
confidence: 99%
“…Following his work, Green and Osher [8] obtained a generalised formula with respect to the curvature of all C 2 convex curves in the plane. These inequalities play a critical role in the curve evolution problem (see, for example, [5,13]). For a fixed convex domain E, Böröczky et al [3] rediscovered the generalised case of (1.4) in relative geometry, that is,…”
Section: Introductionmentioning
confidence: 99%